Theocentric Humanism in Islamic Education: Building Tolerance in a Multicultural Society - Sugeng Darmono; Mahmutarom; Sari Hernawati; Ifada Retno (The Future of Education Journal, 2026)
Islamic Religious Education (PAI) in the contemporary era faces complex challenges in maintaining harmony amid the currents of pluralism and the potential for social polarization. This study employs a qualitative method with a literature review approach. The novelty of this research lies in offering a synthesis between humanistic thought and Islamic transcendental values, which are practically manifested in PAI learning practices. The implementation of theocentric humanism values in PAI learning results in: (a) curriculum reconstruction from a textual approach to a contextual human-centered approach, (b) interactive dialogue that fosters constructive curiosity, and (c) teacher role modeling as humanistic educators. In the model of internalizing theocentric humanism values that effectively builds a tolerant character in society, there are three core stages: (a) the transcendence stage (orientation setting), (b) the humanization stage (empathy and action), and (c) the liberation stage (character independence). In conclusion, the implementation of theocentric humanism values in Islamic Religious Education (PAI) is proven effective in transforming students’ attitudes from passive tolerance to active tolerance. An effective model for internalizing theocentric humanism values in fostering sustainable tolerant character is the Three-Pillar Approach: Transcendence, Humanization, and Liberation.